OPTIMIZATION OF THE LEGAL REGULATION IN THE CONTEXT OF SOCIAL-ECONOMIC DEVELOPMENT - Y. A. Tikhomirov (Russian Journal of Economics and Law, 2015)
Objective: to develop conceptual theoretical-legal provisions and scientific recommendations to optimize legal regulation and increase efficiency of public administration. Methods: universal dialectical method of cognition, and general and private law research methods based on it. Results: in the article, a system of measures on legal regulation optimization under current conditions is proposed. Particular attention is drawn to the need for consistent implementation of the existing legal norms by public authorities and business structures, the appropriate combination of public law and private law regulation methods, for provision of systematic connection between normative legal acts of different sectors. The effectiveness of legal development forecasts in the legislative process is proved, the recommendations on the analysis and evaluation of legal risks are given, the appropriateness of the legal experiment at different levels is justified. Scientific novelty: the mechanism of legal regulation optimization in the context of socio-economic development has been developed and introduced into scientific use. Practical value: the research results can be used in scientific, legislative and law-enforcement activities, in the educational process of higher educational institutions.